Book review: Whittaker, J.K., del Valle, J.F., and Holmes L. (Eds). (2015). Therapeutic residential care for children and youth: Developing evidence-based international practice. London: Jessica Kingsley. 392pp, ISBN 978184905792 - Jonathan Stanley (Scottish Journal of Residential Child Care)
The authors of this edited book 'believe that properly designed and monitored Therapeutic Residential Care represents one critical form of specialized mental health treatment' to be located in a broader array of child and family services' (p.25). To make this a reality, this book shows the need for providers/ practitioners to deploy multiple evidence-based interventions; whether for a specific or milieu setting, there needs to be diagnostic-specific, efficacious interventions enabling the right placement for the right child the first time he or she requires substitute care.